Current status of human papillomavirus vaccination implementation in central and eastern Europe - Seme, Katja (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2013)
We present a review of the current implementation status of vaccination against human papillomaviruses (HPV) and available data concerning the burden of HPV infection and HPV type-specific distribution in 16 central and eastern European countries: Albania, Bosnia and Herzegovina, Bulgaria, Croatia, the Czech Republic, Estonia, Montenegro, Poland, Romania, Serbia, Slovakia, Slovenia, and The Former Yugoslav Republic of Macedonia. At least one current HPV prophylactic vaccine is registered in all central and eastern European countries except Montenegro. Six counties Bulgaria, the Czech Republic, Latvia, Romania, Slovenia, and Former Yugoslav Republic of Macedonia have integrated the HPV vaccination into their national immunization program and currently provide routine vaccination free of charge to the primary target population. Ten countries have not integrated HPV vaccination into the national immunization program. The key reasons for lack of implementation of HPV vaccination into the national immunization program are the high vaccine cost and negative public perception. Vaccination of males is not recommended in any country in the region.
Keywords: centralna in vzhodna Evropa; cepljenje; HPV virusi